The Privatization of State-Owned Enterprises in Islamic Perspective: Case of Indonesia (Global Journal of Management and Business Research, 2019)
In Indonesia, the last few years have seen the privatization of many industries previously owned by the state. The surge was requirement of International Monetary Fund (IMF) to lend its fund in order to support Indonesian economy after monetary crises between 1997 and 1999. However, this phenomenon causes some novel polemics amidst stakeholders. Most of nation"s wealth is brought by multinational companies to overseas without rendering great benefit to citizen. Therefore, inhabitant cannot savour many adventages from their abundant natural resources. In line with this privatization case, Islam as a way of life which is universal and comprehensive has a particular discussion on assets ownership that should be utilised according to its status. There are three concepts of ownership in Islam, namely individual, public and government ownership. The main objective of this paper is to point out the best scheme of natural resources ownership, whether should be owned by public, private or state based on siyāsah sharī"ah approach. The author utilizes descriptive qualitative methodology to find the appropriate pattern of natural resources management in Indonesia, particularly firms which manage the basic need of human being.
Keywords: privatization; natural resources; privatization of state-owned enterprises